2015
DOI: 10.1074/jbc.m114.601146
|View full text |Cite
|
Sign up to set email alerts
|

The Proangiogenic Effect of Iroquois Homeobox Transcription Factor Irx3 in Human Microvascular Endothelial Cells

Abstract: Background: Transcription regulation is essential for angiogenesis, but the role of Irx3 in this process remains to be defined.Results: Irx3 promotes endothelial cell migration and tip cell specification through VEGF-Notch signaling.Conclusion: Irx3 is a novel proangiogenic mediator of endothelial cell migration and cell fate.Significance: Manipulation of Irx3 may provide novel therapeutic strategies in adult vascular pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Whether these mechanisms are involved in the deregulation of IRX3 in HCC needs further investigation. Moreover, IRX3 as a transcriptional factor has been reported to act as either an activator or suppressor of gene expression (23)(24)(25). The functional transcription targets of IRX3 remain to be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these mechanisms are involved in the deregulation of IRX3 in HCC needs further investigation. Moreover, IRX3 as a transcriptional factor has been reported to act as either an activator or suppressor of gene expression (23)(24)(25). The functional transcription targets of IRX3 remain to be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that IRX3 has the potential to promote tumor progression in liver cancer . Studies have shown that VEGF can stimulate the expression of IRX3 in human microvascular endothelial cells, suggesting that IRX3 may contribute to tumor angiogenesis in cancer . IRX4 inhibited cell proliferation, suggesting its tumor‐suppressive effect in prostate cancer and oral squamous cell carcinoma …”
Section: Introductionmentioning
confidence: 92%
“…19 Studies have shown that VEGF can stimulate the expression of IRX3 in human microvascular endothelial cells, suggesting that IRX3 may contribute to tumor angiogenesis in cancer. 20 IRX4 inhibited cell proliferation, suggesting its tumorsuppressive effect in prostate cancer and oral squamous cell carcinoma. 21,22 A previous study showed that IRX5 promoted G1/S-phase transition in vascular smooth muscle cells via CDK2-dependent activation, 23 and IRX5 negatively regulated the transforming growth factor β (TGF-β) pathway, thus promoting the transformation of adenoma to cancer.…”
mentioning
confidence: 99%
“…We then went on to examine a link between Irx3b and Notch, as the Irx factors have been implicated as both positive and negative regulators of Notch signalling (Dominguez & de Celis, 1998;Scarlett, Pattabiraman, Barnett, Liu, & Anderson, 2015). In addition, Notch has recently been linked to CS gland development (B. E. Drummond, Li, Marra, Cheng, & Wingert, 2016) and Notch components are expressed in CS cells (Fig.S4).…”
Section: Irx3b Suppresses Cs Cell Formationmentioning
confidence: 99%
“…This may occur by promoting one Notch-Ligand pairing over another or by altering the strength of the Notch signal. It is also interesting to note that cross-regulatory interactions between Notch and Irx3 have been shown in human microvascular endothelial cells where Irx3 induces expression of Delta-like ligand 4 but is in turn repressed by the Notch mediator Hey1 via direct binding to the Irx3 promoter(Scarlett et al, 2015). How the proposed repressive effects of Irx3b on Notch signalling are overcome so that the DE-to-CS transdifferentiation event can be initiated at the appropriate time during development remain to be determined in future studies.…”
mentioning
confidence: 99%